2018
DOI: 10.1007/s00428-018-2381-6
|View full text |Cite
|
Sign up to set email alerts
|

Gastric gland mucin-specific O-glycan expression decreases as tumor cells progress from lobular endocervical gland hyperplasia to cervical mucinous carcinoma, gastric type

Abstract: Gastric gland mucin-specific O-glycans are unique in having α1,4-linked N-acetylglucosamine (αGlcNAc) attached to MUC6. We previously reported decreased expression of αGlcNAc relative to MUC6 in gastric and pancreatic neoplasms, but its significance in cervical glandular lesions remained unclear. Here, we analyzed MUC5AC, MUC6, αGlcNAc, and p16 expression in 9 lesions of mucinous carcinoma, gastric type with minimal deviation adenocarcinoma (GAS-MDA), 5 of GAS with nonMDA (GAS-nonMDA), 14 of typical lobular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…We previously reported decreased αGlcNAc expression not only in cancer but in pre-malignant lesions of the human stomach, pancreas and uterine cervix 23,25,29 . In the latter, αGlcNAc expression decreases from typical LEGH to atypical LEGH or MDA 30 . These results indicate that decreased αGlcNAc expression is related to tumor progression from pre-malignant to a malignant status.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously reported decreased αGlcNAc expression not only in cancer but in pre-malignant lesions of the human stomach, pancreas and uterine cervix 23,25,29 . In the latter, αGlcNAc expression decreases from typical LEGH to atypical LEGH or MDA 30 . These results indicate that decreased αGlcNAc expression is related to tumor progression from pre-malignant to a malignant status.…”
Section: Discussionmentioning
confidence: 97%
“…In pancreas, we observed significantly decreased αGlcNAc expression relative to MUC6 not only in invasive carcinoma but in its pre-malignant lesions, intraductal papillary mucinous neoplasm and pancreatic intraepithelial neoplasia 25,29 . Furthermore, we recently reported that αGlcNAc and MUC6 are co-expressed in typical LEGH, but αGlcNAc expression is reduced relative to MUC6 in atypical LEGH and minimal deviation adenocarcinoma (MDA) 30 . These findings support the idea that reduced αGlcNAc expression relative to MUC6 marks progression from pre-malignant lesions to cancers showing pyloric gland phenotypes in stomach, pancreas and uterine cervix and that αGlcNAc functions as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…It is also expressed in the endocervix. Yamanoi et al found that MUC5AC was largely expressed in typical LEGH, atypical LEGH, GAS-MDA, and GAS-nonMDA [26]. Thus, we speculated that MUC5AC could be expressed in other adenocarcinomas and might be used for the differential diagnosis of adenocarcinoma and squamous carcinoma.…”
Section: Introductionmentioning
confidence: 85%
“…It is also expressed in the endocervix. Yamanoi et al found that MUC5AC was largely expressed in typical LEGH, atypical LEGH, GAS-MDA, and GAS-nonMDA [24]. Thus, we speculated that MUC5AC could be expressed in other adenocarcinomas and might be used for the differential diagnosis of adenocarcinoma and squamous carcinoma.…”
Section: Introductionmentioning
confidence: 85%